Legal nature of due diligence measures under the anti-money laundering legislation - Shevchenko, M. V. (Аналітично-порівняльне правознавство, 2025)
It is indicated that for the unhindered use and disposal of money or other assets obtained as a result of criminal activity, as well as to reduce the likelihood of their detection and return to their rightful owners, it is necessary to separate such property from the original crime and introduce it into legal economic circulation, creating the appearance of the legal origin of these assets. The article indicates that, in addition to covering the needs of clients and increasing the competitiveness of their services, obliged entities are to perform a wide range of analytical and investigative activities that are not directly related to assessing solvency and good faith of clients to determine the feasibility of establishing business relationships with them. Instead, that activities are carried out to ensure the conditions for the identification and recovery of assets of criminal origin, to facilitate the investigation of a predicate criminal offense and to achieve other goals of the anti-money laundering legislation, which lie entirely in public domain and the implementation of which rests on a state being its inherent function. Moreover, to collect information about clients and their financial transactions in order to carry out due diligence on them, obligated entities may contact not only the clients themselves within the framework of business relations with them. They may as well submit requests for information, which have a special binding status and may be submitted in accordance with the relevant provisions of the anti-money laundering legislation to the National Bank of Ukraine, the National Securities and Stock Market Commission, executive authorities, law enforcement agencies, state registrars. In light of this, it seems reasonable to assume that there is a case of the imposition of government functions on the basis of the anti-money laundering legislation on entities of the financial sector of the economy and some other private entities. Moreover, the due diligence measures, primarily some additional and enhanced due diligence measures, by their nature, as well as by the scale and depth of studying and documenting the reputation and other circumstances of the client’s activities, are close to investigative operations.